Handbook of Public Finance 2005
DOI: 10.1007/1-4020-7864-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Growth in the Real Size of Government Since 1970

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“… See Bird (1970),Kau and Rubin (1981),Borcherding (1985),Mueller (2003),Ferris and West (1996), andBorcherding et al (2004).9 We are indebted to Keith Acheson for pointing this out.10 Exports plus imports as a fraction of GNP vary from 0.30 to about 0.88 in the sample.11 Including LnPOP, or alternatively omitting LnPOP and LnAGRIC (which is also highly correlated with real income LnRYPC) results in a similar pattern of results as are presented inTable 3.…”
supporting
confidence: 80%
See 1 more Smart Citation
“… See Bird (1970),Kau and Rubin (1981),Borcherding (1985),Mueller (2003),Ferris and West (1996), andBorcherding et al (2004).9 We are indebted to Keith Acheson for pointing this out.10 Exports plus imports as a fraction of GNP vary from 0.30 to about 0.88 in the sample.11 Including LnPOP, or alternatively omitting LnPOP and LnAGRIC (which is also highly correlated with real income LnRYPC) results in a similar pattern of results as are presented inTable 3.…”
supporting
confidence: 80%
“…First, scale economies are not often found in studies of government growth, as noted by Borcherding et al (2004). Moreover, population in Canada is not clearly integrated of order one like the other economic factors.…”
Section: Political Convergencementioning
confidence: 94%
“…On the other hand, authors like Ferris and West (1996), Rodrik (1998a), Cusack (1997), Garrett andMitchell (1999, 2001), Figlio and Blonigen (2000), Grubert (2000), Ferris (2003), Borcherding et al (2004) and Liberati (2007) have found contrasting results in favour of efficiency hypothesis.…”
Section: Review Of Literaturementioning
confidence: 88%
“…While the government sector continues to grow in many economies, Borcherding et al (2004) observe falling government consumption over the last decades for the U.S. and some other highly developed European countries. A shrinking government (and in particular a shrinking welfare state) could be explained as a consequence of increasing fiscal policy competition between national authorities.…”
Section: Final Remarksmentioning
confidence: 98%